BAPTISTSKAJA IDENTIČNOSTʹ MEŽDU TRADICIEJ I TRADICIONALIZMOM = BAPTIST IDENTITY BETWEEN TRADITION AND TRADITIONALISM - Sannikov, Serhij Viktorovyč (Bogoslovskie razmyšlenija, 2020)
The article discusses the concept of tradition in the context of the selfidentification of a religious group using as a key study the practice of Baptist congregations. The author explains the formation of Tradition and analyzes its features, in particular, he is drawn attention to the elasticity of traditions and their hypostatic variability with a relatively constant essentiality. The author shows the features of Baptist traditionalism, its similarity and differences from philosophical traditionalism. He draws close attention to the distinction between traditionalism, fundamentalism and conservatism, and points out the characteristic features of each of these phenomena. In particular, the article emphasizes the dangers of losing tradition. It’s points out that losing their tradition, any group loses its own self-identification and dissolves in a wide community.The article analyzes the essence of the Baptist tradition, which is revealed in Christocentrism, Biblicisms, individual freedom and separation of Church and State; in discipleship, community and missionary orientation. The author notes that tradition is a deeper system-forming factor for a group than name of the group or their denominational affiliation. At the same time, the article draws attention to the negative effect conversions tradition into traditionalism, which saves more form, then content.Baptist traditionalism, like philosophical traditionalism, is trying to return modern Baptist congregations to the "ideal" past of the apostolic church. However, in practice, traditionalism tries to return the forms of worship, and some doctrines, not to the primitive church time, but only for several generations ago. The author believes that a more positive contribution to the development of the religious community is made by conservatism, which is focused on preserving the essential ideas of the Baptist tradition and on it contextualizing for the new conditions of the society. Article emphasized that in the life of Baptist congregations, traditionalism and conservatism play an important preserving role, entering into a dialectical tension with progressivism and modernism, which are aimed at denying all tradition. The difficult interaction of all these trends ensures the self-identification of a particular confessional group and specifically Baptist. Author pay much attention to demonstrates traditionalism in history of Evangelic-Christian Baptist in fSU and to highlighting some features of traditionalism are revealed in contrast to the general Tradition of this religious group.